The Effect of Brand Image, Packaging, Location, and Service Quality on Customer Satisfaction in Raihan Bakery and Cake Shop Products - Hou, Amin (CV. Rayyan Dwi Bharata, 2023)
The research aims to determine the effect of brand, packaging, location, and service quality on customer satisfaction in bakery and cake shop products. This type of research is quantitative research, the population in this study is a sample of 100 people. Data analysis techniques in this study used multiple regression data analysis and hypothesis testing. The results of this study are Brand Image, packaging has a positive and significant effect on customer satisfaction in Raihan bakery cake and Shop, location has a positive and significant effect on customer satisfaction in Raihan bakery cake and Shop, service quality has a positive and significant effect on customer satisfaction in Raihan bakery cake and shop, and packaging, location and service quality have a positive and significant effect on customer satisfaction in Raihan bakery cake and shop